Orthodontic extrusion of subgingival carious teeth - Bye-ri Han; Mi-yeon Kim (Elsevier, 2023)
Introduction: The restoration of extensively carious teeth has been challenging, especially when the caries extends below the gingival margin. In this case, the teeth with subgingival caries were restored using orthodontic extrusion. Case Description: A 66-year-old female patient presented with complaint of cavity of the upper anterior teeth. The patient had received endodontic treatment on #11, 12 teeth and crown restoration on #11 tooth. At the clinical examination, upper right central incisor presented a distal root caries and upper right lateral incisor presented a loss of mesial wall owing to caries extend below the gingival margin. To start, old crown removal of #11 tooth was performed. Lingual buttons were bonded to the #11, 12 teeth, resin-wire splint was placed to the adjacent teeth, and extrusive force was provided by elastic thread. After 6 weeks, around 4mm of extrusion had been achieved. And crown lengthening procedure with osteotomy was performed. Residual caries were removed. A fiber post (Snowpost, Abrasive) was cemented with adhesive (Singlebond Universal, 3M ESPE) and resin cement (RelyX Ultimate, 3M ESPE) and core (LuxaCore Dual, DMG) was built up. Finally Porcelain fused to zirconia crowns were cemented. After 1-year follow up, the teeth presented satisfactory functional and esthetic outcomes. In addition, the periodontal tissues remained healthy. Discussion: This case included extensive decay of multiple teeth, and each tooth had discrepancy of gingival margin. Thus, osteotomy was accompanied with orthodontic extrusion considering the location of gingival margin. Conclusion/Clinical Significance: Orthodontic extrusion is a valuable treatment option in the management of subgingival carious teeth.